Efisiensi Penggunaan Bahan Bakar Biodiesel B40, untuk Kebutuhan Dunia Industri dan Transportasi - Maulana Banurea; Dhafa Ikhwana Yusda Tanjung; Maulana Pratama; Ikhsan Arifin; Muhammad Rangga Ramadhan Dongoran (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2025)
An environmentally friendly fuel with great potential for use in transportation and industry is B40 biodiesel. It is a mixture of 60% diesel and 40% biodiesel. With an emphasis on engine performance, environmental impact, and financial incentives, the study assesses how beneficial its use can be. According to the findings, B40 biodiesel burns better and produces fewer carbon emissions compared to pure diesel because it has a higher cetane number. However, fuel consumption may increase due to the much lower energy content of biodiesel. B40 requires more maintenance to avoid hygroscopic effects, but it has been shown to improve lubrication and support heavy equipment operations in industrial environments. Implementing B40 has several benefits, including the ability to reduce greenhouse gas emissions.